Validation of the scales for assessing swimming abilities of students at the Faculty of Humanities and Social Sciences in Zagreb - Gošnik, Jelka (Array, 2011)
The aim of this study is to validate two scales for assessing swimming abilities of undergraduate students. The scale 1 is divided in five categories according to Grčić-Zubčević (1996), while the new scale 2, based on Špehar, Gošnik and Fučkar Reichel (2010), consists of twelve questions, with the range of answers from 1 to 5 (don’t know, weak, medium, good and very good), that students use to self-assess their swimming abilities. This research was conducted on a sample of 949 freshmen at Faculty of Humanities and Social Sciences in academic year 2010/11. Multiple regression analysis shows high, statistically significant (p<0, 05), level of correlation (R=0, 72 ; p=0, 0000) between two methods or scales for evaluation of swimming abilities of students. The beta coefficient demonstrates that statistically significant contribution to correlation provide variables 5, 6, 8, 9, 10, 11 and 12 (elaborated in section 4). This confirms the hypothesis that self-assessment of swimming abilities according to the scale 2 is a good predictor of results based on self-assessment based on the scale 1. In other words, the both scales are valid for evaluation of specific parameters.